2020
DOI: 10.1007/s00345-020-03476-6
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 and financial toxicity in patients with renal cell carcinoma

Abstract: Purpose To ascertain renal cell carcinoma (RCC) financial toxicity on COVID-19 during the COVID-19 crisis as patients are struggling with therapeutic and financial implications. Methods An online survey was conducted from March 22 to March 25, 2020. It included baseline demographic, clinicopathologic, treatment-related information, anxiety levels related to COVID-19, questions related to financial concerns about COVID-19 as well as the validated 11-item COST measure. Results Five-hundred-and-thirty-nine pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
22
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 15 publications
0
22
1
Order By: Relevance
“…Given the global economic hardship brought about by the pandemic, the untoward financial consequences experienced by patients with cancer have been exacerbated. An online survey of 539 renal cell carcinoma patients across 14 countries found that 59% of respondents doubted that their retirement and savings assets would cover the cost of treatment and 23% "did not feel in control of their financial situation" [45].…”
Section: Discussionmentioning
confidence: 99%
“…Given the global economic hardship brought about by the pandemic, the untoward financial consequences experienced by patients with cancer have been exacerbated. An online survey of 539 renal cell carcinoma patients across 14 countries found that 59% of respondents doubted that their retirement and savings assets would cover the cost of treatment and 23% "did not feel in control of their financial situation" [45].…”
Section: Discussionmentioning
confidence: 99%
“… 14 An estimated 7.7 million Americans have lost their jobs and employer‐sponsored health insurance, and current evidence suggests that the pandemic worsens cancer‐related financial toxicity for cancer survivors. 15 , 16 Indeed, cancer survivors may be “doubly hit” as they face co‐occurring financial hardships from the pandemic and their cancer care. 17 Cancer survivors with transient or temporary employment, which is more likely in young adulthood, have been reported to be at higher risk for the negative economic effects of COVID‐19.…”
Section: Introductionmentioning
confidence: 99%
“…Kidney cancer (renal cell carcinoma, RCC) is the seventh most common cancer and has shown a sustained increase in global prevalence, thereby presenting an increasing burden on health systems, governments, and, most of all, individual patients and their families [1] , [2] , [3] . Although therapies have improved for both early-stage and late-stage RCC, little is known about variations in the patient experience and best practices among countries.…”
mentioning
confidence: 99%